Development of energy-saving technology to support functioning of the lead-acid batteries - Chaikovskaya, Eugene (Eastern-European Journal of Enterprise Technologies, 2017)
Based on mathematical and logical modeling, a technological support system for changing the battery capacity based on the prediction of voltage variation in measuring the temperature of electrolyte in the volume of the batteries was developed in the com-position of a technological system for battery operation. The developed technology makes it possible: to control operational capacity of the accumulator battery in order to obtain a functional assessment of change in the total charge and discharge voltage; to obtain an integrated reference estimation of change in the charge and discharge volt-age; to develop an integrated system for assessing a change in the voltage of the battery, which enables maintaining capacity of the accumulator battery when measuring the temperature of electrolyte at the input to the battery. The limiting temperature change of electrolyte, – 35 °C, was determined at charging with direct current supply and a limit-ing voltage change for a further charge and discharge was established with a change in the consumption of electric energy. The use of an integrated system for the estimation of voltage change obtained based on the alignment between electrochemical and diffusion processes of discharge and charge makes it possible to take timely decisions on recharg-ing to prevent recharge and unacceptable discharge. Coordination of the electrochemi-cal and diffusion processes that accompany charging and discharging of the battery makes it possible, for example under conditions of functioning of a wind power plant with a capacity of 10 kW, to reduce the cost of production of energy and the payback period of the wind power plant by up to 25 % due to a reduction of the charge period and prevention of gas formation.